2021
DOI: 10.3389/fphys.2021.678184
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs in the Second Trimester From Pregnant Women Who Subsequently Developed Preeclampsia: Potential Candidates as Predictive Biomarkers and Pathway Analysis for Target Genes of miR-204-5p

Abstract: MicroRNAs (miRNAs) play an important role in the pathophysiology of preeclampsia (PE). However, the expression of circulating miRNAs was not analyzed in the second trimester of pregnancy, a period of major relevance to identify predictive biomarkers for PE. Therefore, we examined the expression profiles of 84 circulating miRNAs using a PCR array in plasma collected between 20 and 25 weeks of gestation from pregnant women, who subsequently developed PE and those who remained healthy during pregnancy, randomly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…As such, the evaluation of miRNA biomarker variability in heterogeneous or comorbid populations is a challenge. For example, the studies of this review included a mix of male and female subjects, however sex-based differences may influence miRNA expression [ 55 ] including the regulation of gonadal hormones [ 56 ], menstrual cycles [ 57 ] and pregnancy [ 58 ]. The diet of subjects may also affect miRNA expression by contributing external miRNAs that are indistinguishable from endogenous miRNAs [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, the evaluation of miRNA biomarker variability in heterogeneous or comorbid populations is a challenge. For example, the studies of this review included a mix of male and female subjects, however sex-based differences may influence miRNA expression [ 55 ] including the regulation of gonadal hormones [ 56 ], menstrual cycles [ 57 ] and pregnancy [ 58 ]. The diet of subjects may also affect miRNA expression by contributing external miRNAs that are indistinguishable from endogenous miRNAs [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, analysis of embryo culture media from IVF programs showed a reduced expression of hsa‐mir‐20a‐5p in samples from low quality embryos (Abu‐Halima et al., 2020). The use of miRNA as reproductive biomarkers brings new possibilities for non‐invasive predictors, like hsa‐mir‐103a‐3p, which showed higher expression in plasma from pregnant women with severe preeclampsia (Luizon et al., 2021). Moreover, miR‐10a‐5p modulates BDNF expression in human follicular fluid and could indicate embryo quality on days 3 and 5, potentially aiding embryo selection and IVF success rates (Zhang, Su, et al., ; Zhang, Zhang, et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an effect of gonadal steroids on miRNAs expression (Morgan & Bale, 2012). Menstrual cycles and pregnancy are among the events that also have an effect on total circulating miRNA profiles (Rekker et al, 2013;Luizon et al, 2021).…”
Section: Other Individual Factors (External Factors)mentioning
confidence: 99%